Reviews of Physiology, Biochemistry and Pharmacology
DOI: 10.1007/s10254-004-0031-7
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa ExoS and ExoT

Abstract: ExoS and ExoT are bi-functional type-III cytotoxins of Pseudomonas aeruginosa that share 76% primary amino acid homology and contain N-terminal RhoGAP domains and C-terminal ADP-ribosylation domains. The Rho GAP activities of ExoS and ExoT appear to be biochemically and biologically identical, targeting Rho, Rac, and Cdc42. Expression of the RhoGAP domain in mammalian cells results in the disruption of the actin cytoskeleton and interference of phagocytosis. Expression of the ADP-ribosyltransferase domain of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
208
0
1

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(218 citation statements)
references
References 62 publications
9
208
0
1
Order By: Relevance
“…The expression of a type-III secretion system (T3SS) by P. aeruginosa and T3SS-and T6SS-secreted effector proteins have been reported to be required for the cellular invasion and are supposed to influence the growthphase dependent cellular uptake of P. aeruginosa (11,(42)(43)(44)(45). However, our data suggest that initial membrane curvature and wrapping of the bacterium by the host PM depends neither on a bacterial secretion system nor on secreted effector proteins.…”
Section: Discussionmentioning
confidence: 65%
“…The expression of a type-III secretion system (T3SS) by P. aeruginosa and T3SS-and T6SS-secreted effector proteins have been reported to be required for the cellular invasion and are supposed to influence the growthphase dependent cellular uptake of P. aeruginosa (11,(42)(43)(44)(45). However, our data suggest that initial membrane curvature and wrapping of the bacterium by the host PM depends neither on a bacterial secretion system nor on secreted effector proteins.…”
Section: Discussionmentioning
confidence: 65%
“…The highest specificity for RhoA, B, and C was observed with C3cer (Wilde et al 2003). The asparagine modification is a unique property of C3 toxins, since many bacterial ADP-ribosyltransferases modify arginine residues (e.g., cholera toxin, Pseudomonas exoenzyme S and T, C. botulinum C2 toxin; Moss and Vaughan 1977;Barbieri and Sun 2004;Vandekerckhove et al 1988) or a cysteine residue (e.g., pertussis toxin; West et al 1985). Recently, it was shown that the three isoforms C3stau1, 2, and 3 of Staphylococcus aureus differ in their substrate specificity.…”
Section: Introductionmentioning
confidence: 99%
“…It secretes four toxins by a TTSS: ExoS, ExoT, ExoU and ExoY (Barbieri & Sun, 2004;FinckBarbancon et al, 1997;Frank, 1997;Hauser et al, 1998;Yahr et al, 1996Yahr et al, , 1998. ExoS can induce a cytotoxic effect (Olson et al, 1999), and is associated with the ability to produce lung damage and poor outcome from P. aeruginosa infection (Roy-Burman et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The GAP domain of ExoS had no effect on DNA synthesis. Many targets of the ExoS ADPRT domain action have been identified, including members of the small GTPase family proteins, such as Ras, Rab, Ral and Rap, as well as vimentin, and the GAP domain within its own N-terminal region Barbieri & Sun, 2004). These studies have demonstrated the effects of ExoS on the activation and interaction of small GTPases with downstream effectors.…”
Section: Introductionmentioning
confidence: 99%